VISIONARY LEADERSHIP IN DEVELOPING MADRASAH COMPETITIVENESS AT MAN 2 PONDOK PESANTREN DARUL ULUM REJOSO JOMBANG - Indana, Nurul; Eko Sujianto , Agus; Masrokan Mutohar , Prim (LP3M Universitas Islam Zainul Hasan Genggong, 2023)
Leadership is visionary leadership. Visionary leadership is leadership whose main work is focused on engineering a challenging future. With the visionary leadership of the madrasah head, he is able to color Islamic educational institutions so that Islamic education experiences an increase in realizing progress so that it is able to compete strictly, even being able to outperform the progress achieved by other educational institutions. This research uses a qualitative approach with a case study type with a multi-case design. The research location chosen was MAN 2 Pondok Pesantren Darul Ulum Rejoso. The results of the study state that the head of the madrasa is a leader in increasing competitiveness, namely by elaborating the vision into missions so that the objectives of the madrasa are achieved, formulating goals and targets for the quality of the madrasa to be achieved, analyzing opportunities, challenges, strengths and weaknesses of madrasah diniyah, being transparent in the use of the budget, in decision making, applying visionary leadership. Focus on a challenging future, a superior change agent. organizational direction. professional trainer in his leadership he head of the madrasa describes a visionary leader who is able to become a professional trainer. This is realized from literacy programs and moving classes, which translate into institutional success. The visible indicators of madrasah competitiveness are: the number of applicants exceeds the capacity of the available study rooms. Therefore, the greater the number of registrants at the madrasa, the higher the competitiveness of the madrasa. Have academic or non-academic achievements,